Identification of effective dilutions of dental herbal remedy with antimicrobial activity - Shulga, L (Annals of Mechnikov’s Institute, 2020)
Introduction.There are different ways to solve the problem of resistance of microorganisms. One of them includes an increase of the drug dose, thereby arising adverse reaction, andtheotherincludesa development of the new antimicrobial agents, where no less focus is given to drugs on basis of medicinal plant raw materials owning to the antimicrobial activity confirmed by scientific researches. Herbal remediesareincludedintotreatmentcodesagainst infectious and inflammatory dental diseases, however while there is a persistent growth of mouth inflammatory diseases we have signals for expediency of new ones to be produced. Our prior studies deal with developing the tincture conventionally called Casdent, substantiation of using such three types of pharmacopeia medicinal plant raw materials as: licorice roots, sedge cane rootstocks, burnet rootstocks with its roots. The previously determined antimicrobial and antifungal activity of Casdent tincture is insufficient for recommending the use thereof in the therapeutic dentistry, as the external use provides for an additional dilution thereof with saliva, crevicular fluids, exudates. The aim is to identify the most efficient dilutions of Casdent tincture to substantiate its reasonable application in dentistry. Materials and methods. Target of examination is Casdent tincture as developed by employees of the Department of General Pharmacy and Drug Safety of the Institute of Pharmacy Professionals Qualification Improvement of the National University of Pharmacy. Control is the herb preparation: Stomatophyt («Phytopharm Klenka S.A.», Poland). The work is performed at the State Establishment «Mechnikov Institute of Microbiology and Immunology of the National Academy of Medical Sciences of Ukraine» through use of museum and clinical strains of microorganisms,which daily cultures have been grown on the respective digest media according to the requirements of the State Pharmacopoeia of Ukraine. The twofold serial dilution method (microbial load has been determined at 0.5 unit as per McFarland scale) has been used. The obtained data of survey are statistically processed according to Student. Results and discussion. Inhibiting concentration of Casdent tincture diluted in (1:32) has been empathized in respect to: S. epidermidis, S. pneumoniaе, B. subtilis and candida fungi: C. albicans, C. catenulata (C. rugosa)Sclar C-27, C. albicans clinical strain No. 23. For strains: S. aureus, S. haemolyticus, S. mutans clinical strain No. 45, E. coli, P. аeruginosa, the minimal inhibiting concentration value corresponds to dilution of (1:16). Although a similar trend of antimicrobial activity is ascertained at comparing the antimicrobial effect’s values of Casdent tincture and those of the control: Stomatophyt, the compared preparation is valid as diluted in (1:32) only in respect to S. aureus and C. аlbicans, and in respect to other cultures – as diluted in (1:16). Additional researches of antimicrobial properties of solutions Casdent and Stomatophyt: (1:10), (1:20) have made it possible to identity the minimal inhibiting and bactericide concentration thereof. Based on the level of antimicrobial activity of Casdent tincture it is determined that it is highly competitive with the level of the imported preparation: Stomatophyt, and upon examination of values of bactericide concentration of Casdent dilutions: (1:20) for S. aureus,S. pneumoniaе, B. subtilis, somehow excels similar dilutions of Stomatophyt. Conclusion. The effective solutions of Casdent tincture are identified: 1 teaspoonful (5 ml) of Casdent tincture per 100 ml of water – for bacterial static effect and 2 teaspoonfuls (10 ml) in the same volume of water – for bactericide effect. The results of microbiological examinations testify to prospectivity of the developed tincture and will be taken into account when issuing the recommended application thereof in therapeutic dentistry.